2020
DOI: 10.1017/ice.2020.465
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized SARS-CoV-2 transmission risk: Surgical or N95 masks?

Abstract: Based on available evidence, the COVID-19 virus is thought to spread through close contact and droplet transmission. However, some have debated that it could be airborne. Airborne transmission occurs when particles of less than 0.5 μm within droplets spread through exhaled air via a process called aerosolisation. These particles can remain in the air for long periods and can disseminate over distances further than 1 meter. In the context of COVID-19, airborne particles can occur during certain aerosolised-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Several reports suggest that aerosol transmission is indeed a non-negligible mode of SARS-CoV-2 transmission and that respirators may provide additional protection compared to surgical masks [ 17 19 , 21 ]. On the other hand, case reports have suggested that surgical masks are equivalent to respirators in protecting HCW from SARS-CoV-2 infection [ 22 , 23 ]. These supposedly contradictory findings can be reconciled when considering a particular feature of SARS-CoV-2, namely its high overdispersion [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest that aerosol transmission is indeed a non-negligible mode of SARS-CoV-2 transmission and that respirators may provide additional protection compared to surgical masks [ 17 19 , 21 ]. On the other hand, case reports have suggested that surgical masks are equivalent to respirators in protecting HCW from SARS-CoV-2 infection [ 22 , 23 ]. These supposedly contradictory findings can be reconciled when considering a particular feature of SARS-CoV-2, namely its high overdispersion [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies were at high risk of bias (n=18/21) ( 16 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ) primarily due to the potential for recall bias (e.g. use of self-report surveys), participation bias (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies reported the rate of SARS-CoV-2 infection in HCWs who wore surgical masks compared to those who wore respirators ( 16 , 24 , 26 , 27 , 28 , 29 , 31 , 33 , 35 , 37 , 38 , 40 ). Overall, a similar percentage of HCWs wearing respirators (1,398/15,598 = 8.96%) and surgical masks (1,698/17,947 = 9.46%) acquired SARS-CoV-2 infection ( Fig 2 ).…”
Section: Results Synthesismentioning
confidence: 99%
“…It has been suggested that use of non-invasive ventilation strategies may increase transmission of SARS-COV-2 to healthcare workers, placing them at risk during care and adding strain to the healthcare system when isolation is required 2,26 . Although appropriate personal protective equipment may provide adequate protection for some healthcare workers when NIV strategies are used, existing studies are predominantly from early 2020 there is a lack of comparative studies available on this topic [67][68][69][70][71][72][73][74][75][76][77][78] .…”
Section: Discussionmentioning
confidence: 99%